THE USE OF ADAPTIVE DIGITAL TECHNOLOGIES IN TEACHING MATHEMATICS TO STUDENTS WITH SPECIAL EDUCATIONAL NEEDS IN SPAIN AND ECUADOR - Gallardo Herrerías, Celia (2025)
This study examines the impact of adaptive digital technology on teaching mathematics for special educational needs (SEN) students in Spain and Ecuador. It assesses technology capital-based inclusive education models using a mixed-methods approach. The objectives are: (1) to assess the impact of adaptive software on SEN students’ learning and engagement, (2) to examine challenges and opportunities across different learning contexts, and (3) to make recommendations on teacher training and accessibility enhancement. Evidence confirms that these tools improve mathematical capability and independence considerably, with long-term impacts. Success is, however, dependent on teachers’ training, investment in infrastructure, and balanced policy support. Research recommends an inclusive strategy to ensure the maximum utilization of these tools and offer quality and inclusive education to SEN students.